Comparative analysis of Dipodomys species indicates that kangaroo rat hindlimb anatomy is adapted for rapid evasive leaping. Issue 3 (14th October 2021) - Freymiller, Grace A.; Whitford, Malachi D.; Schwaner, M. Janneke; McGowan, Craig P.; Higham, Timothy E.; Clark, Rulon W.
Abstract: Body size is a key factor that influences antipredator behavior. For animals that rely on jumping to escape from predators, there is a theoretical trade‐off between jump distance and acceleration as body size changes at both the inter‐ and intraspecific levels. Assuming geometric similarity, acceleration will decrease with increasing body size due to a smaller increase in muscle cross‐sectional area than body mass. Smaller animals will likely have a similar jump distance as larger animals due to their shorter limbs and faster accelerations. Therefore, in order to maintain acceleration in a jump across different body sizes, hind limbs must be disproportionately bigger for larger animals. We explored this prediction using four species of kangaroo rats ( Dipodomys spp.), a genus of bipedal rodent with similar morphology across a range of body sizes (40–150 g). Kangaroo rat jump performance was measured by simulating snake strikes to free‐ranging individuals. Additionally, morphological measurements of hind limb muscles and segment lengths were obtained from thawed frozen specimens. Overall, jump acceleration was constant across body sizes and jump distance increased with increasing size. Additionally, kangaroo rat hind limb muscle mass and cross‐sectional area scaled with positive allometry. Ankle extensor tendon cross‐sectional area also scaled with positive allometry. Hind limb segment length scaled isometrically, with the exception of the metatarsals, which scaled with negative allometry. Overall, these findings support the hypothesis that kangaroo rat hind limbs are built to maintain jump acceleration rather than jump distance. Selective pressure from single‐strike predators, such as snakes and owls, likely drives this relationship. Abstract : During evasive jumps from a simulated attack, kangaroo rat jump acceleration was constant across a range of body sizes while jump distance increased with increasing size. Additionally, kangaroo rat hind limb muscle mass and cross‐sectional area scaled with positive allometry. These findings suggest that kangaroo rat hind limbs are built to maintain jump acceleration rather than jump distance. Selective pressure from single‐strike predators, such as snakes and owls, may drive this relationship.